2015
DOI: 10.4172/2167-7972.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition of Wines Elaborated from Organic and Non-Organic Grapes

Abstract: The aim of this work was to study the evolution of volatile compounds during the alcoholic fermentation of organic and non-organic grapes. To do this, grapes were cultivated using organic and non-organic grapes; their tasting showed some differences between both types of Monastrell grapes. Throughout the alcoholic fermentation, the samples of organic grapes had higher concentration of total alcohols but lower concentration of esters and acids than the samples of conventional ones. Therefore, the volatile compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…In this quarter, we can find the wines elaborated with the native strains G3, G9, and G19 from Cellar A, G465 from Cellar F, and G513, G514, G515, and G518 from Cellar E. In this case, a connection point between the strains named above is that their cellars of origin utilize spontaneous fermentation and an organic system of wine production. In accordance with these results, Lorenzo et al [55] observed that the volatile composition of wines from organic or non-organic grapes was considerably different. In particular, they concluded that the OAVs of wines from ecologically-grown grapes had more chemical and floral aromas, while the wines from conventional practices presented a fruitier character.…”
Section: Principal Component Analysissupporting
confidence: 53%
“…In this quarter, we can find the wines elaborated with the native strains G3, G9, and G19 from Cellar A, G465 from Cellar F, and G513, G514, G515, and G518 from Cellar E. In this case, a connection point between the strains named above is that their cellars of origin utilize spontaneous fermentation and an organic system of wine production. In accordance with these results, Lorenzo et al [55] observed that the volatile composition of wines from organic or non-organic grapes was considerably different. In particular, they concluded that the OAVs of wines from ecologically-grown grapes had more chemical and floral aromas, while the wines from conventional practices presented a fruitier character.…”
Section: Principal Component Analysissupporting
confidence: 53%